Mitochondria, immunosenescence and inflammaging: a role for mitokines? - Conte, Maria; Martucci, Morena; Chiariello, Antonio; Franceschi, Claudio; Salvioli, Stefano (Seminars in immunopathology, 2020)
A global reshaping of the immune responses occurs with ageing, indicated as immunosenescence, where mitochondria and mitochondrial metabolism play an important role. However, much less is known about the role of mitochondrial stress response in this reshaping and in particular of the molecules induced by such response, collectively indicated as mitokines. In this review, we summarize the current knowledge on the role of mitokines in modulating immune response and inflammation focusing on GDF15, FGF21 and humanin and their possible involvement in the chronic age-related low-grade inflammation dubbed inflammaging. Although many aspects of their biology are still controversial, available data suggest that these mitokines have an anti-inflammatory role and increase with age. Therefore, we hypothesize that they can be considered part of an adaptive and integrated immune-metabolic mechanism activated by mitochondrial dysfunction that acts within the framework of a larger anti-inflammatory network aimed at controlling both acute inflammation and inflammaging.